Immaterial-Material Reality, Computation and Architectural Design - Cinici, Sebnem Yalinay (ECAADE-EDUCATION & RESEARCH COMPUTER AIDED ARCHITECTURAL DESIGN EUROPE, 2009)
Computational design technologies are providing the conditions to advance the ways of design thinking and making. Though there are diverse approaches in the current architectural ideations and applications, the images produced by these technologies grab the most attention. These images mostly show off how different architecture can be by the use of computation. This paper will be criticizing this existing condition by discussing the change in the concept of reality with the advance of digital technologies, and its effects on our understanding of architectural materiality. So besides being a critique on current 'picture' of architecture, this paper aims at dragging attention to the implicit potential of the current computational technologies in a different perspective.
Keywords: Computation; immaterial; material; architectural space; reality.; Architecture